Bidirectional interactions between trading behaviors and carbon prices in European Union emission trading scheme. (1st July 2019) - Wang, Jiqiang; Gu, Fu; Liu, Yinpeng; Fan, Ying; Guo, Jianfeng
Abstract: We investigate the bidirectional interactions between trading behaviors and carbon prices in the first carbon market, i.e., European Union Emissions Trading Scheme (EU ETS). The trading behaviors of the emitting companies are classified into 'compliance trading' and 'non-compliance trading' based on their positions, and the behaviors of financial intermediaries are quantified according to the changes in their inventories. We use two AR-EGARCH models and an ARMA-GARCH model to assess the bidirectional interactions between trading behaviors and carbon prices, and three empirical findings are derived. First, since emitting companies can predict their actual demand of a complete phase, 'compliance trading' is not affected by the annual nominal compliance demand of allowances, while 'non-compliance trading' is influenced by financial intermediaries' inventories and 'compliance trading'. Second, the allowance prices do have asymmetry effects on the volatilities of emitting companies' trading behaviors. Third, 'compliance trading' and the inventories of the financial intermediaries explain the trend of carbon prices, while 'non-compliance trading' explains the volatility of carbon prices. The findings could provide valuable managerial implications for managing the carbon markets. Graphical abstract: Image 1 Highlights: Bidirectional interactions between trading behaviors and carbon prices are analyzed. 'Compliance trading' is not influenced by the nominal compliance demand in a year. 'Non-compliance trading' is influenced by intermediaries and 'compliance trading'. The volatilities of trading behaviors can be explained by carbon prices. Carbon pricing is explained by participants' trading behaviors.